ANALISIS PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DIPO LOKOMOTIF SIDOTOPO SURABAYA BERDASARKAN ISO 45001:2018 MENGGUNAKAN METODE FAILURE MODE EFFECT ANALYSIS (FMEA) - Tuhu Agung Rachmanto; Lintang Putri Rafsanjani (EnviroUS, 2022)
Dipo Locomotive Sidotopo Surabaya is a place to maintainance and inspection of locomotives to pull a series of trains. In order to protect its workers, this company tries to make SMK3 the main focus of the company to create a safe working atmosphere and prevent occupational diseases. This study aims to determine the application of SMK3 and the failure factors that occur in the locomotive repair process using the FMEA method. The failure factors are given an assessment of severity, occurrence, and detection. The three assessments are then calculated with the RP) to reduce which risk has the highest level of potential. Based on research that has been carried out, the identification of hazards that have the highest risk are electric shock, interacting with high-temperature pipes, being exposed to oil splashes, releasing hazardous gases and interacting with flammable materials.